A readiness check for regionalization of engineering - Schaeffler, Thomas; Kodes, Rudolf; Foehr, Matthias; Luder, Arndt; Götz, Johannes; Franke, Jörg (IECON Proceedings (Industrial Electronics Conference), 2014)
Regionalization of software and hardware engineering in international project business is a key driver for the success of multinational companies. These companies usually act as prime contractors and therefore have to execute large engineering projects across several countries. This requires a shift of the whole or at least a portion of their engineering value chain to a foreign country (regionalization). Since a shift of the value chain means a major change in the project execution process, a regionalization initiative is of high risk for the company. For that reason, we describe an approach to effectively check the extent to which a given company is ready for regionalization. The goal of this readiness check is to identify areas with need for action and preparatory work before starting a regionalization initiative. The check is structured alongside the fundamental questions as to why regionalization should be performed, what should be regionalized, who should do it, where regionalization should take place and which conditions apply. It provides management with a cockpit-like overview of the current state and addresses required action fields. By measuring the extent of regionalization readiness, important insight into the regionalization effort can be gained, such as the need for investment into the early phases and the required balance between all participating parties (stakeholders). Examples of practical use of the readiness check are presented and directions for further research are shown.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Engineering; Hardware; Project business; Readiness check; Regionalization; Software